COVID 19 vaccination as a trigger of acute genital ulcers in an immunocompromised adolescent-case study and literature review - Karolina Pokora; Karolina Kowalczyk; Robert Peterek; Marlena Cwynar; Rafał Stojko; Paweł Madej; Agnieszka Drosdzol-Cop (BMC, 2024)
Abstract Acute genital ulcers can affect females of all ages. In children, they often appear as an emergency and remain a diagnostic challenge for pediatricians, gynecologists and dermatologists. Prompt diagnosis and identification of disease- related factors help to implement appropriate treatment. Firstly, it is crucial to properly compile the past medical history of the patient. Past infectious, autoimmune, malignant or traumatic conditions, as well as vaccinations may contribute to the occurrence of acute genital ulcers. Moreover, new infectious agents, such as severe acute respiratory syndrome coronavirus 2 and vaccinations against Coronavirus disease of 2019, may play a significant role in the development of atypical clinical symptoms. Here we present a case of a 12-year-old girl with acute genital ulcers. Additional symptoms accompanying the ulcer included: abdominal pain, nausea, vomiting, dysuria, vulvar pain and fever. Blood test showed leukocytosis, especially neutrophilia and monocytosis and increased levels of c-reactive protein and procalcitonin. Serological tests for the most common infections were negative. Moreover, the patient had a history of autoimmune diseases. She had periodic fever, aphthous stomatitis, pharyngitis, and adenitis syndrome, and IgA vasculitis, also known as Henoch-Schönlein purpura in her past medical history. Additionally, she was vaccinated against SARS-CoV-2 shortly before the lesions appeared.